Kant and the Our Father - Rovira, Rogelio (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
In the effort to reconcile the thesis according to which prayer, as an inner ritual service of God, is not a religious duty with the fact that Jesus commanded and taught to pray, Kant argues that the Our Father is a prayer that renders all prayer dispensable, including itself. The analysis of the meaning of this statement, seemingly paradoxical, brings to light Kant’s thesis according to which the Our Father is a completely moral prayer and invites to rebuild, following the philosopher’s suggestions, the moral significance of the seven petitions contained in the Lord’s Prayer. The Our Father, thus interpreted, appears as the epitome of what Kant means by religion within the boundaries of mere reason.